Early evolution of the land plant circadian clock. Issue 2 (28th February 2017) - Linde, Anna‐Malin; Eklund, D. Magnus; Kubota, Akane; Pederson, Eric R. A.; Holm, Karl; Gyllenstrand, Niclas; Nishihama, Ryuichi; Cronberg, Nils; Muranaka, Tomoaki; Oyama, Tokitaka; Kohchi, Takayuki; Lagercrantz, Ulf
Summary: While angiosperm clocks can be described as an intricate network of interlocked transcriptional feedback loops, clocks of green algae have been modelled as a loop of only two genes. To investigate the transition from a simple clock in algae to a complex one in angiosperms, we performed an inventory of circadian clock genes in bryophytes and charophytes. Additionally, we performed functional characterization of putative core clock genes in the liverwort Marchantia polymorpha and the hornwort Anthoceros agrestis . Phylogenetic construction was combined with studies of spatiotemporal expression patterns and analysis of M. polymorpha clock gene mutants. Homologues to core clock genes identified in Arabidopsis were found not only in bryophytes but also in charophytes, albeit in fewer copies. Circadian rhythms were detected for most identified genes in M. polymorpha and A. agrestis, and mutant analysis supports a role for putative clock genes in M. polymorpha . Our data are in line with a recent hypothesis that adaptation to terrestrial life occurred earlier than previously expected in the evolutionary history of charophyte algae. Both gene duplication and acquisition of new genes was important in the evolution of the plant circadian clock, but gene loss has also contributed to shaping the clock of bryophytes.